Penerapan Asas Hukum Pidana Islam dalam Mengatasi Kejahatan Kontemporer - Anggraini, Sabna; Pulungan, Sofia Zuhro Zein; Rahma, Ainur; Puspita, Asti Nurul; Solin, Rina; Marpaung, Zaid Alfauza (Mediation : Journal of Law, 2024)
This article examines the application of Islamic criminal law standards in the context of contemporary crime anticipation. Islamic criminal law, which is based on ethical and moral values, offers a relevant approach to dealing with various forms of crime today, such as cybercrime, bullying based on fear, and insults. This research distinguishes several standards of Islamic criminal law, enumerates standards of justice, legal certainty and practicality, and looks at how these standards can be coordinated into a positive legal framework to make legal enactment more successful. Additionally, this article emphasizes the importance of justice and beneficial remedies in dealing with offenders, in order to re-establish exasperated social relationships. Thus, the application of Islamic criminal law standards is expected to provide comprehensive and relevant regulations in facing the challenges of modern crime, while still paying attention to human rights standards and human values.